Depth Without a Surface: Observations From a "Finger Spinner" Depth Illusion. (November 2017) - Crognale, Michael A.
A trending novelty toy that is spun between the fingers induces a striking depth illusion from specular reflections. Further examination of the phenomenon suggests that when surface features are obscured by spinning, depth from disparity of reflections is enhanced.